Effects of linear and undulating periodization of strength training in the acceleration of skater children - Jaimes, Diego A.R. [UNESP]; Contreras, Dennis; Jimenez, Alejandra M.F. [UNESP]; Orcioli-Silva, Diego [UNESP]; Barbieri, Fabio A. [UNESP]; Gobbi, Lilian T.B. [UNESP] (FapUNIFESP (SciELO), 2019)
Aim: This study aimed to compare the effects of linear periodization (LP) and undulating periodization (UP) of strength training on acceleration in skater children. Methods: Twenty-nine girls (9.67±1.29 years-old, 34.47±8.06kg, 1.39±0.13m) were distributed into two groups: linear periodization group (LPG, n=14) and undulating periodization group (UPG, n=15). Six levels of progressive training were designed based on activities such as multi-jumps, plyometrics, sled towing, and facilitated exercises. The training lasted 16 weeks, with a 1-h session on three nonconsecutive days per week. The acceleration was recorded by digital videography following the major trochanter of the femur, at four moments and under two conditions: static (SS) and dynamic start (DS) in a rectilinear path. Statistical significance was set at 5%. Results: ANOVA indicated group*moment interaction in SS and DS for velocity (F3,81=7.883; p<0.001; pη2=0.226; F3,81=2.36; p=0.078; pη2=0.08-trend, respectively) and acceleration (F3,81=3.96; p=0.011; pη2=0.128; F3,81=2.92; p=0.039; pη2=0.098, respectively). Both groups increased velocity in SS and DS (UPG/SS: 1st=4.07, 2nd=9.75, 3rd=8.91, 4th=9.25m/s; LPG/SS: 1st=4.27, 2nd=7.13, 3rd=7.61, 4th=7.99m/s; UPG/DS: 1st=8.30, 2nd=8.73, 3rd=8.12, 4th=9.27m/s; LPG/DS: 1st=8.20, 2nd=8.31, 3rd=7.90, 4th=8.96m/s) and acceleration (UPG/ SS: 1st=2.00, 2nd=8.69, 3rd=4.71, 4th=5.02m/s2; LPG/SS: 1st=2.37, 2nd=3.39, 3rd=3.68, 4th=4.12m/s2; UPG/DS: 1st=1.78, 2nd=1.97, 3rd=1.65, 4th=2.46m/s2; LPG/DS: 1st=1.67, 2nd=1.70, 3rd=1.48, 4th=1.93m/s2). Conclusion: Both strength training periodization protocols were effective in developing acceleration and velocity in girl skaters over 16 weeks; however, UP was more efficient than LP for improving acceleration.
Keywords: Girls; Inline speed skating; Load intensity; Performance; Strength training periodization